(untitled) (European Journal of Pure and Applied Mathematics, 2023)
The main aim of this work is to introduce and study the notions of ideal direct product d-algebras, d-ideal direct product d-algebras, sub-direct product d-algebras, edge direct product and positive implicative direct product d-algebras and investigate their characterizations.